ANALISIS KOMPONEN-KOMPONEN UTAMA SERTA FUNGSI DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM - Br Tarigan, Ira Wahyuni; Saragih, Elida; Halimah, Siti (IMTIYAZ: Jurnal Ilmu Keislaman, 2024)
In this investigate, we look at the Islamic devout instruction educational programs of the foremost vital parts of the educational system because it may be a apparatus for accomplishing instructive objectives and a direct for the execution of instruction at all instructive levels. The educational modules of Islamic instruction is known as manhaj, which alludes to the clear way taken after by instructors and understudies to create information, abilities and states of mind. Four fundamental components were created for the educational modules: destinations, materials, strategies and evaluation, and organized This think about employments a writing review or bibliographic investigate strategy. A writing survey is an exertion to gather information from sources such as books, articles, diaries, or other archives on a point related to the investigate being conducted. Inquire about on the part of educational modules in all zones is exceptionally empowering. This alludes to the tradition of passing down science from the older era to the more youthful era. The educational modules should be overhauled to meet the wants of a world where different sees collide with devout, logical and inventive values. Keywords:  Main Components; Function; Curriculum.